Hip arthroscopy for intra-articular pathology: a systematic review of outcomes with and without femoral osteoplasty. Issue 9 (22nd December 2011) - Kemp, Joanne L; Collins, Natalie J; Makdissi, Michael; Schache, Anthony G; Machotka, Zuzana; Crossley, Kay
Abstract : Background: Arthroscopy is increasingly used to improve pain and function in athletes with hip joint pathology. Surgical techniques have evolved to utilise arthroscopic femoral osteoplasty to address potential morphological contributors to pathology. Purpose: Investigate pain and function outcomes following hip arthroscopy with and without femoral osteoplasty in individuals with intra-articular hip pathology. Study design: Systematic review. Methods: A comprehensive search strategy identified studies that evaluated the outcome over at least 3 months following arthroscopy for intra-articular hip pathology, using patient-reported outcomes of pain and/or function. Methodological quality was evaluated (Downs and Black scale), and effect sizes calculated when sufficient data were available. Results: Twenty-nine studies of moderate methodological quality were included. Of 16 studies investigating arthroscopy alone, two studies showed large effects (3.12–5.46) at 1–2 years. Pain reduction and functional improvement (median 47%) were consistently reported by the remaining 14 studies up to 10 years postsurgery. Of 15 studies investigating arthroscopy with osteoplasty, nine papers showed mostly large effects (0.78–2.93) over 6–28 months. Adverse events were minimal (7% of participants, 12 studies, predominantly transient neuropraxia (83%)). Conclusion: Current evidence indicates that hip arthroscopy can significantly reduce pain and improve function in patients with intra-articular hip pathology. While benefits of arthroscopy alone can persist up to 10 years postsurgery, effects of osteoplasty beyond 3 years need to be established. Future studies should investigate rehabilitation in this population, and the impact of surgery on development of osteoarthritis.